Isoliquiritigenin Enhances the Beige Adipocyte Potential of Adipose-Derived Stem Cells by JNK Inhibition - Hanbyeol Moon; Jung-Won Choi; Byeong-Wook Song; Il-Kwon Kim; Soyeon Lim; Seahyoung Lee; Ki-Chul Hwang; Sang Woo Kim (Molecules, 2020)
Human adipose-derived stem cells (hASCs) can be isolated from fat tissue and have attracted interest for their potential therapeutic applications in metabolic disease. hASCs can be induced to undergo adipogenic differentiation in vitro by exposure to chemical agents or inductive growth factors. We investigated the effects and mechanism of differentiating hASC-derived white adipocytes into functional beige and brown adipocytes with isoliquiritigenin (ILG) treatment. Here, we showed that hASC-derived white adipocytes could promote brown adipogenesis by expressing both uncoupling protein 1 (UCP1) and PR/SET Domain 16 (PRDM16) following low-dose ILG treatments. ILG treatment of white adipocytes enhanced the expression of brown fat-specific markers, while the expression levels of c-Jun N-terminal kinase (JNK) signaling pathway proteins were downregulated. Furthermore, we showed that the inhibition of JNK phosphorylation contributed to white adipocyte differentiation into beige adipocytes, which was validated by the use of SP600125. We identified distinct regulatory effects of ILG dose responses and suggested that low-dose ILG induced the beige adipocyte potential of hASCs via JNK inhibition.